COMPLIANCE WITH IRON TABLET CONSUMPTION AND MACRONUTRIENT INTAKE IN RELATION TO ANEMIA IN FEMALE STUDENTS AT SMAN 2 KOTA JAMBI - Merlisia, Mery; Setyarsih, Liani; Lubis, Izmi Arisa Putri; Fatimah, Putri; Sundjaya, Tonny (Ridwan Institute, 2025)
Background: Adolescent girls are vulnerable to anemia due to increased iron needs during menstruation and often inadequate dietary intake. This study aimed to analyze the relationship between compliance with Iron Tablet (TTD) consumption and macronutrient intake with the incidence of anemia in female students. Methods: This cross-sectional study was conducted at SMAN 2 Kota Jambi with 24 randomly selected female students. Data were collected through a compliance questionnaire, 3x24-hour food recall, and hemoglobin level measurement. Chi-square test was used for analysis. Results: A total of 62.5% respondents were non-compliant with TTD consumption. Macronutrient intake was generally poor: 95.8% lacked energy intake, 79.2% lacked carbohydrates, 66.7% lacked protein, and 87.5% lacked fat. Anemia prevalence was 45.8%. No significant relationship was found between TTD compliance and anemia (p=0.916). However, fat intake was significantly associated with anemia incidence (p<0.05). Conclusion: Anemia in adolescent girls is not significantly associated with iron tablet compliance but is related to fat intake. Interventions should target improving diet quality and fat adequacy alongside supplementation.